Modelling Radial Oscillations of a Bubble in a Spherical Liquid-Filled Elastic Solid - Dana A. Mohammedameen; Kawa M.A. MANMI; Waleed H. Aziz (Zanco Journal of Pure and Applied Sciences, 2022)
In this paper, equation of a spherical bubble oscillations in Newtonian and viscous fluid with considering compressible fluid flow in a spherical liquid-filled elastic solid was developed. The exact solution of the linearisation and the numerical solution of the equation have been derived and compared. Then numerical calculations are performed to investigate the effects of compressibility parameter for gas and acoustic bubbles. We conclude that the amplitude of bubble radius oscillations increases with and the effects of is accumulating. Further, the discrepancy between the exact and numerical solutions increases with time when . However, the difference was not changed when the is smaller than . Dual frequency is also considered in the acoustic environment.